Artificial intelligence in food production and services: A bibliographic review of research published from 2014 to 2024 (Research, Society and Development, 2025)
Increasingly, the area of food is on the rise in multidisciplinary scientific studies, to develop professional improvement activities, and this in all phases of food production, from customer service to the creation of new products, where artificial intelligence (AI) is revolutionizing and demanding that these professionals be updated to cover current market needs. This article aims to present an exploratory literature review as a data collection technique, investigating artificial intelligence applied in the food and beverage sector, emphasizing the possibilities offered by artificial intelligence today, its importance, and the benefits and difficulties of its implementation, from production to consumer services. The search was done on the Thomson Reuters Web of Science platform database and published internationally. A total of 24 articles were found, 4 of which were aligned with the object of study and deserve to be highlighted for demonstrating the possibilities of AI tools linked to the topic in question. The research showed that the discovery and application of artificial intelligence techniques in the food and beverage sector, both in production and consumer services, leads to better results and excellence in product and service agility. However, there are still difficulties in applying these AIs due to the inabilities of professionals, who need more training in the area in question, and rejection of use by some producers and consumers.